How Does Reverse Design Drive the Deep Integration of Ideological and Political Education into Accounting Courses?—Practical Logic, Experience Transfer, and Pathways for Promotion - Duan, Qingqing; Wang, Shuo (Journal of Educational Research and Policies, 2026)
As ideological and political education in courses shifts from conceptual advocacy to systematic implementation, there is an urgent need to resolve the methodological challenge of “how to interweave” ideological and political objectives with professional knowledge. Based on reverse design theory, this paper proposes that “interweaving” differs from “integration” in its academic connotation: integration is the goal, while interweaving is the method; only through precise interweaving can deep integration be achieved. Taking the accounting major as the practical field, this study constructs a trinity-based interweaving framework comprising “value objectives—knowledge modules—assessment indicators.” Through methodological experimentation with a core accounting course, it addresses four key issues—top-level disengagement, evaluation vacuity, resource misallocation, and the two-dimensional dilemma—by systematically presenting the operational mechanisms of four pathways: objective mapping, evaluation front-loading, resource restructuring, and bidirectional empowerment. Additionally, the WHERETO framework is introduced to optimize the design of learning activities. Building on this foundation, the study distills general methodological elements, demonstrates the feasibility of transferring this framework to other accounting courses, and establishes a methodological construction paradigm characterized by “originating from one course and validated across multiple courses.” The study found that reverse design provides a methodological tool for course-based ideological and political education to transition from conceptual advocacy to standardized procedures; the definition of the “mutual embedding” concept establishes identifiable observation anchors for evaluating the effectiveness of ideological and political education; and the replicability of the methodology offers an operational practical paradigm for the systematic development of course-based ideological and political education in accounting-related majors.